(untitled) (Communications in Computational Physics, 2025)
The re-splitting δf method (Ye et. al CPC 2020) has been implemented into the global semi-Lagrangian gyrokinetic code NLT (Lei Ye et al. 2016, JCP) for the simulations of electromagnetic micro-turbulence in tokamak plasmas. The re-splitting method can be incorporated with the numerical Lie transform method, which is an essential numerical scheme for NLT code, to mitigate the cancellation problem appears in the gyrokinetic p_||-formulation with gyrokinetic ions and drift-kinetic electrons. With this method, the ion temperature gradient mode (ITG), the kinetic ballooning mode (KBM) and trapped electron mode (TEM) are simulated by NLT and the results are well benchmarked with other gyrokinetic simulation codes.